Kontribusi Tabungan Emas Pegadaian Syariah terhadap Ketahanan Finansial Masyarakat dalam Perspektif Ekonomi Syariah - Adibah Badzlina; Sirajul Arifin (Studia Economica : Jurnal Ekonomi Islam, 2025)
This research aims to examine the contribution of gold savings in strengthening the financial resilience of society from an Islamic economic perspective. Pegadaian Syariah's gold product is an Islamic financial innovation that provides access to gold investment with small denominations, using the murabahah contract for buying and selling transactions and the wadiah contract for safekeeping mechanisms. The method used is a literature study, examining reputable journals, proceedings, official reports, DSN-MUI fatwas, and Sharia Pawnshop publications. The study results indicate that gold savings serve as a safe, transparent, and halal investment instrument, and are effective as a hedge against inflation and global economic factors. Recent gold price data showing a consistent upward trend strengthens gold's role as a safe haven. From a Sharia economic perspective, gold savings reflect the value of the maqashid al-syariah, particularly hifz al-mal (protection of wealth), while also supporting Sharia financial literacy and inclusion. Compared to other Sharia instruments, gold savings are simpler, more inclusive, and easier for the general public to understand. Thus, Pegadaian Syariah's gold savings can be positioned as an important pillar in building the financial resilience of the community based on Sharia principles